Design of a mode converter for efficient light-atom coupling in free space - Sondermann, Markus; Maiwald, Robert; Konermann, Hildegard; Lindlein, Norbert; Peschel, Ulf; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2007)
In this article, we describe how to develop a mode converter that transforms a plane electromagnetic wave into an inward-moving dipole wave. The latter one is intended to bring a single atom or ion from its ground state to an excited state by absorption of a single photon wave packet with near-100% efficiency. © 2007 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.design